Disenchantment narrative in anti-superstition fiction of the late Qing dynasty - Ding, Sing Jek (2015)
Anti-superstition themes, which were unconventional and rarely found in classical Chinese literature, first gained popularity in the late Qing dynasty. These fictional writings possessed characteristics specific to their times and their societal background, and embodied an ideology for reformation. As such, whether from the perspective of the history of the Chinese fiction or the late Qing culture, these writings are worthy of scholastic research. This thesis attempts to explore, firstly, the narrative style and characteristics of the late Qing anti-superstition fiction on the basis of the “disenchantment” concept proposed by Max Weber and, secondly, how these narrative approaches brought into prominence the central theme and the enlightenment thoughts in the writings. These attempts are intended to bring about a more rational and accurate understanding of the characteristics and the implicit thinking of the late Qing anti-superstition fiction. This thesis begins with an exploration of the factors contributing to, and the historical background behind, the rise in popularity of the anti-superstition narratives of the late Qing dynasty, then follows with a comparative study of six representative late Qing anti-superstition novels, in order to identify and categorise the various forms of “superstition” in them. The thesis goes on to explore how the authors of these novels criticised and revealed the mysteries of the mentioned superstitious practices, and then to generalise and summarise the features common to the disenchantment narratives of these novels and finally to discuss the “anti-ignorance” intentions of these disenchantment narratives. The results of this research show that similar disenchantment strategies and narrative styles were used in these anti-superstition fiction even though they were penned by six different authors. The disenchantment narratives in these fiction targeted five lines of thoughts, namely the nonexistence of gods and deities, vicious practices of the monks and priests, revelation of the tricks of the fortune tellers and wizards, the scams of the feng shui masters and the tragic consequences of superstitious behaviours. Additionally, the viewpoint of “ignorance is the mother of superstition”, the importance given to the anti-superstition mission of the enlightened, as well as the from-charmed-to-enlightened transformation of the fictional characters — all these bring forth a very clear anti-ignorance intentions of the authors. If disenchantment is at the core of the anti-superstition fiction, then the implicit objective and motivation is the eradication of the ignorance of the common citizens, a pre-requisite to the development of China into a modern and rational society.